Development of In-Hospital Outcomes in Patients undergoing Transcatheter Aortic Valve Implantation (TAVI) at an Interdisciplinary Heart Center: A Single-Center Experience of 489 Consecutive Cases - Rana, Mukaram; Niethammer, Margit; Sellin, Christian; Dörge, Hilmar; Eggebrecht, Holger; Schächinger, Volker (Cardiology and Cardiovascular Medicine, 2023)
Background: Transcatheter Aortic Valve Implantation (TAVI) has emerged over time, reflected in appropriate adjustments in the European Society of Cardiology (ESC) guidelines in 2007, 2012 and 2017. Objective: The aim of this study was to analyze in-hospital outcomes after TAVI in the development within a single heart center over a period of 10 years depending on adjustments in the guidelines, infrastructural and procedural determinants Methods: 489 consecutive patients who underwent TAVI from 2010 and 2019 at our center were analyzed retrospectively. Patients were divided into 3 groups of different treatment circumstances depending on guidelines adjustments and local infrastructural progress (group 1: 2010-2015 (n = 132), group 2: 2016-2017 (n = 155), group 3: 2018-2019 (n = 202). The primary endpoint was defined as all-cause in-hospital mortality. Secondary endpoints were selected according to the Valve Academic Research Consortium (VARC)-2 definitions. Multivariate logistic regression analysis was performed to determine predictors of in-hospital mortality. Statistical significance was assumed for p < 0.05. Results: 489 patients (346 (70.8 %) transfemoral and 143 (29.2 %) transapical) underwent TAVI. Comparing periods (group 1 vs. 2 vs. 3) age (82.1 ± 6.2 vs. 82.5 ± 4.8 vs. 81.1 ± 5.1 years, p = 0.012) and EuroSCORE II (8.4 ± 6.0 vs. 5.8 ± 4.9 vs. 5.5 ± 5.0 %, p < 0.001) declined over time. Rates of in-hospital mortality decreased significantly (9.1 % vs. 5.8 % vs. 2.5 %, p = 0.029), especially with observed-to-expected mortality ratios indicating a disproportionate decline of in-hospital mortality (1.08 vs. 1.00 vs. 0.45). Furthermore, post-procedural complications, such as acute kidney injury stage 3 (10.6 % vs